A Life with Light, Statistics and Differintegrals. Issue 7 (October 2016) - Uozumi, Jun
In this issue we also continue our custom of inviting the winner of the JCNIR Award to contribute an overview of his or her research interests in near infrared (NIR) spectroscopy. Dr Jun Uozumi is the winner of 2016 JCNIR award. The award is made annually by the Japan Council for Near Infrared Spectroscopy (JCNIRS) on the basis of the contribution of an individual to NIR research in Japan and the whole Asian continent. The award ceremony will be held on 1 December 2016 at the 5 th Asian NIR Symposium (joint event with the 32 nd Japanese NIR Forum) in Kagoshima city, Japan.